2021
DOI: 10.1155/2021/5531959
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Microvascularization Analysis Using Swept-Source Optical Coherence Tomography Angiography in Optic Chiasmal Compression

Abstract: Purpose. To evaluate the vessel density (VD) of the radial peripapillary capillary (RPC) network using swept-source optical coherence tomography angiography (SS-OCTA) “en face” images of eyes with chiasmal compression caused by brain tumors before and after decompressive surgery compared with healthy controls. Methods. A cross-sectional study was conducted in 12 patients with chiasmal compression confirmed by neuroimaging. Sixteen healthy participants were also included. All patients with chiasmal compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies have found reduced RPCP and super cial macular capillary plexus density in PA patients [21][22]. This reduction is speculated to result from tumor growth compressing the optic chiasm, causing axoplasmic ow obstruction and reduced blood supply, leading to neural atrophy and ganglion cell death, which ultimately manifests as retinal vasoconstriction [23]. Our study identi ed reduced blood ow density in both the optic disc RPCP and all layers of the macular region, which aligns with the results of Gilda Cennamo and others [22].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have found reduced RPCP and super cial macular capillary plexus density in PA patients [21][22]. This reduction is speculated to result from tumor growth compressing the optic chiasm, causing axoplasmic ow obstruction and reduced blood supply, leading to neural atrophy and ganglion cell death, which ultimately manifests as retinal vasoconstriction [23]. Our study identi ed reduced blood ow density in both the optic disc RPCP and all layers of the macular region, which aligns with the results of Gilda Cennamo and others [22].…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has suggested that the growth of pituitary tumors results in optic chiasm compression, leading to reduced axoplasmic transportation and blood supply [29,30]. The resulting nerve fiber atrophy and apoptosis of ganglion cells may lead to reduced oxygen demand in the retina, thus leading to blood vessel atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [24] found that the RPC vascular density in the nasal and temporal quadrants was correlated to the RNFL thickness in the corresponding quadrants in 31 patients with brain tumors with optic chiasm compression. After studying 12 patients with brain tumors with optic chiasm compression, Ghezala et al [29] found that their RPC was significantly lower than healthy people. Our results support these previous results.…”
Section: Discussionmentioning
confidence: 99%